Penerapan Combined Compromise Solution Method Dalam Penentuan Penerima Beasiswa - Yustina Meisella Kristania (PT. Tech Cart Press, 2023)
This study aims to solve the problem of determining scholarship recipients through a decision support system with output in the form of ranking using the Combined Compromise Solution Method. The application of the Combined Compromise Solution (CoCoSo) method in determining scholarship recipients will result in a comparison of the scores of all students who register to receive scholarships from schools. So that through the decision support system developed it can produce prospective scholarship recipients according to predetermined criteria and the selection process does not take long because the decision support system built is equipped with a web-based application using Laravel 8 which is used to determine scholarship recipients. Calculations for determining scholarship recipients using the Combined Compromise Solution (CoCoSo) show that the results of calculating the final score of the 1st scholarship recipient received a final score of 2.7031 obtained by Dwi Adhawati, the 2nd scholarship recipient received a final score of 1.9111 obtained by Muhammad Ferdi, and the 3rd scholarship recipient with a final score of 1.8684 was obtained by Muhammad Irfan.